2023
DOI: 10.3390/fermentation9020150
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Nero Antico di Pretalucente Wine and Grape Fungal Microbiota: An Expression of Abruzzo Region Cultivar Heritage

Abstract: The aim of this study was to characterize the ampelographic and genetic profiles of Vitis vinifera L. cv. Nero Antico di Pretalucente and to describe the grape-borne fungal communities. The oenological characteristics and the aroma profile of wine obtained by spontaneous fermentation were also investigated. Microsatellite profiles and ampelographic traits indicated that this cultivar presented a unique profile, and therefore it can be considered a cultivar in its own right and autochthonous of Gessopalena vill… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…In Italy, Perpetuini et al (2022) reported that the common genera of fungi detected in grape samples of Montepulciano d’Abruzzo cultivar (Abruzzo Region, Central Italy) were represented by Hanseniaspora, Aureobasidium, Botrytis, Pichia, Cladosporium and Alternaria. In another work conducted by Perpetuini et al (2023) , it was found that Aureobasidium, Metschnikowia, Hanseniaspora, Botrytis, Cladosporium, Pichia, Alternaria, Epicoccum, Vishniacozyma and Candida were the main genera detected on the minor grapevine cultivar cv. Nero Antico from Chieti (Abruzzo Region, Central Italy).…”
Section: Discussionmentioning
confidence: 96%
“…In Italy, Perpetuini et al (2022) reported that the common genera of fungi detected in grape samples of Montepulciano d’Abruzzo cultivar (Abruzzo Region, Central Italy) were represented by Hanseniaspora, Aureobasidium, Botrytis, Pichia, Cladosporium and Alternaria. In another work conducted by Perpetuini et al (2023) , it was found that Aureobasidium, Metschnikowia, Hanseniaspora, Botrytis, Cladosporium, Pichia, Alternaria, Epicoccum, Vishniacozyma and Candida were the main genera detected on the minor grapevine cultivar cv. Nero Antico from Chieti (Abruzzo Region, Central Italy).…”
Section: Discussionmentioning
confidence: 96%